“A journey undertaken under peculiar circumstances”: The Perilous Escape of William Lyon Mackenzie December 7 to 11, 1837 - Raible, Christopher (Ontario History)

(untitled) (The Ontario Historical Society, 2016)
When his 1837 Upper Canada Rebellion came to a sudden end with the routing of rebels at Montgomery’s Tavern on 7 December, William Lyon Mackenzie was forced to run for his life. With a price on his head, travelling mostly by night—west toward the Niagara Escarpment, south around the end of Lake Ontario and then east across the Niagara peninsula—the rebel leader made his way from a village north of Toronto to safety across the Niagara River in the United States. His journey of more than 150 miles took five days ( four nights) on foot, on horseback, and on wagon or sleigh, was aided by more than thirty different individuals and families. At great personal risk, they fed him, nursed him, hid him, advised him, accompanied him. This article maps Mackenzie’s exact route, identifies those who helped him, and reflects on the natural hazards and human perils he encountered.